2022
DOI: 10.1212/wnl.0000000000200048
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ATN Research Framework With Clinical Profile, Cognitive Decline, and Mortality in Patients With Dementia With Lewy Bodies

Abstract: Background and Objectives:The ATN framework has been developed to categorize biological processes within the Alzheimer’s disease (AD) continuum. Since AD pathology often coincides with dementia with Lewy Bodies (DLB), we aimed to investigate the distribution of ATN profiles in DLB and associate ATN-profiles in DLB to prognosis.Methods:We included 202 DLB patients from the Amsterdam Dementia Cohort (68±7yrs, 19%F, MMSE: 24±3, DAT-SPECT abnormal: 105/119). Patients were classified into eight profiles according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
4
9
0
Order By: Relevance
“…ATN categories were stratified by AD pathologic change without p‐Tau pathology (A+T−N−, A+T−N+), AD pathologic change with p‐Tau (A+T+N−, A+T+N+), non‐AD pathologic change (A−T+N−, A−T−N+, A−T+N+), and normal AD biomarkers (A−T−N−). Interestingly, the same ATN distribution as in our study was previously reported, 30% A+T− and 26% A+T+ 17 . This suggests that not only is there a large proportion of A+ individuals in DLB as previously described, 3,10,17 but many of the A+ individuals do not meet criteria for p‐Tau biomarker thresholds.…”
Section: Discussionsupporting
confidence: 88%
“…ATN categories were stratified by AD pathologic change without p‐Tau pathology (A+T−N−, A+T−N+), AD pathologic change with p‐Tau (A+T+N−, A+T+N+), non‐AD pathologic change (A−T+N−, A−T−N+, A−T+N+), and normal AD biomarkers (A−T−N−). Interestingly, the same ATN distribution as in our study was previously reported, 30% A+T− and 26% A+T+ 17 . This suggests that not only is there a large proportion of A+ individuals in DLB as previously described, 3,10,17 but many of the A+ individuals do not meet criteria for p‐Tau biomarker thresholds.…”
Section: Discussionsupporting
confidence: 88%
“…With respect to the association between plasma ptau181 and treatment response, it is important to note that, in DLB, such elevated plasma levels of phosphorylated tau are associated with more extensive neurodegeneration 6,7,28 and more rapid clinical disease progression. 17,29 This literature is compatible with our observation that elevated plasma ptau181 is associated with poorer cognitive function and greater dementia severity. These findings are also consistent with prior reports of pathology and/or MRI data indicating that patients with DLB and without AD copathology (cortical tau pathology and/or neuritic amyloid plaques) have minimal cortical atrophy, particularly in the medial temporal lobe.…”
Section: Discussionsupporting
confidence: 85%
“…Few studies have previously examined the association between biomarkers in the ATN classification and mortality. A previous study in a population of patients with Lewy body dementia showed that those within the AD continuum had a steeper cognitive decline and shorter survival [ 24 ]. Two studies have also reported an association of brain amyloidopathy assessed on PET amyloid [ 25 ] or neurodegeneration assessed by brain MRI atrophy with a higher risk of mortality [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%